2020
DOI: 10.1080/15368378.2020.1737807
|View full text |Cite
|
Sign up to set email alerts
|

Specific low-frequency electromagnetic fields induce expression of active KDM6B associated with functional changes in U937 cells

Abstract: In this study, we investigated the effects of specific low frequency electromagnetic fields sequences on U937 cells, an in vitro model of human monocyte/macrophage differentiation. U937 cells were exposed to electromagnetic stimulation by means of the SynthéXer ® system using two similar sequences, XR-BC31 and XR-BC31/F. Each sequence was a time series of twenty-nine wave segments. Here, we report that exposure (4 days, once a day) of U937 cells to the XR-BC31 setting, but not to the XR-BC31/F, resulted in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Together with complex dynamics of regulatory signals, modulation of tendon immune biology events, including the switch of macrophage functional phenotypes, may be assisted by external triggers [ 12 ]. Research has shown that the pulsed electromagnetic field (PEMF), a biophysical form of stimulation, accelerates cell differentiation, increases deposition of collagen, and modulates the activation of cell surface receptors, thereby holding relevant contributions for the re-establishment of homeostatic cell functions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together with complex dynamics of regulatory signals, modulation of tendon immune biology events, including the switch of macrophage functional phenotypes, may be assisted by external triggers [ 12 ]. Research has shown that the pulsed electromagnetic field (PEMF), a biophysical form of stimulation, accelerates cell differentiation, increases deposition of collagen, and modulates the activation of cell surface receptors, thereby holding relevant contributions for the re-establishment of homeostatic cell functions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%